A wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm

By adopting the chemical formula of Ba3Gd4-xCrx(PO4)6, a wide spectrum near-infrared fluorescent material with a half-height width of the emission spectrum greater than 300 nm and a quantum efficiency greater than 90% under blue light excitation was prepared, which solves the problem of lack of such materials in the prior art and is suitable for near-infrared LED devices.

CN117384636BInactive Publication Date: 2025-04-11XIAMEN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311321695.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a lack of near-infrared fluorescent materials that can be able to have the main peak and peak position of the emission spectrum greater than 1000 nm under blue light excitation, the half-height width of the emission spectrum greater than 250 nm, and Cr3+, which has stable chemical properties and high quantum efficiency, as the luminescence center.

Method used

The chemical formula of Ba3Gd4-xCrx(PO4)6 is prepared by high-temperature solid phase reaction. Cr3+ is used as an activator to emit near-infrared light under blue light excitation. The main peak-to-peak position of the emission spectrum is greater than 1310 nm, the half-height width of the emission spectrum is greater than 300 nm, and the quantum efficiency under 450 nm blue light excitation is greater than 90%.

Benefits of technology

Under blue light excitation, a wide spectrum near-infrared fluorescent material with a half-height width of the emission spectrum greater than 300nm, with a quantum efficiency greater than 90%, and is suitable for near-infrared LED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117384636B_ABST
    Figure CN117384636B_ABST
Patent Text Reader

Abstract

A wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm, the chemical composition of the fluorescent material is: Ba3Gd 4‑x Cr x (PO4)6, where 0<x<0.5. The material is Cr 3+ It is an activator and emits near-infrared light under blue light excitation. The main peak of the emission spectrum is greater than 1310nm, and the half-width of the emission spectrum is greater than 300nm. The quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material is applied to near-infrared light LED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fluorescent materials, and in particular to a wide-spectrum near-infrared fluorescent material with a half-width of an emission spectrum greater than 300nm. Background Art

[0002] Near-infrared spectroscopy technology has important applications in food testing, facial recognition, optoelectronic control, iris recognition, security monitoring, health testing and 3D sensing. The premise of using near-infrared spectroscopy technology is to have a near-infrared light source that can achieve near-infrared spectral output. The wider the near-infrared spectrum output by the light source, the higher the resolution and the wider the detection range. Common near-infrared light sources are xenon lamps and near-infrared light-emitting diodes. Xenon lamps can achieve continuous coverage of the entire near-infrared region (780-2526nm), but xenon lamps have disadvantages such as large size, short life, and low electro-optical conversion efficiency, which limits their practical application. Near-infrared LED chip technology has problems such as high cost and immature technology. In addition, the half-height width of the emission spectrum of a single near-infrared chip is usually only tens of nanometers. Therefore, if you want to achieve wide near-infrared spectrum coverage, you need to splice multiple LEDs emitting at different near-infrared wavelengths, which will lead to a decrease in the reliability of the resulting near-infrared device.

[0003] Recently, a near-infrared light source technology solution has emerged that realizes near-infrared light output based on a blue light chip combined with a near-infrared fluorescent material. Since the performance of the blue light chip used for excitation is determined, the near-infrared fluorescent material has a decisive influence on the parameters of the near-infrared light source. Therefore, it is of great significance to develop near-infrared fluorescent materials with excellent performance, especially wide spectrum (large emission spectrum half-width). In addition, since the near-infrared spectrum contains a band of 780 to 2526nm, it is obviously difficult for a fluorescent material to completely cover such a wide range of emission spectrum. In order to achieve a near-infrared light-emitting device with a wide spectrum based on LED excitation of near-infrared fluorescent materials, it is necessary to mix near-infrared fluorescent materials with different near-infrared luminescence properties (main peak position of the emission spectrum and wide emission spectrum half-width). However, after the fluorescent materials are mixed, there will be obvious luminescence reabsorption between the fluorescent materials, that is, the light emitted by one near-infrared fluorescent material will be absorbed by another near-infrared fluorescent material, which will inevitably lead to a decrease in the efficiency of the near-infrared light-emitting device. Therefore, the research and development direction of near-infrared fluorescent materials is to develop near-infrared fluorescent materials with different emission wavelengths (main peak positions) and emission spectrum half-widths as wide as possible.

[0004] Cr-doped 3+Near-infrared fluorescent materials are the mainstream of current research on near-infrared fluorescent materials. As stated in non-patent document 1 (Wen-Tse Huang, Veeramani Rajendran, Ming-Hsien Chan, Michael Hsiao, Ho Chang, Ru-Shi Liu, Near-Infrared Windows I and II Phosphors for Theranostic Applications: Spectroscopy Bioimaging and Light-Emitting Diode Photobiomodulation, Advanced Optical Materials, 2023, 11: 2202061), Cr 3+ The emission spectrum of transition elements such as Cr is greatly affected by the crystal field. In different crystal field environments, narrowband (the half-width of the emission spectrum is only a few nanometers) or a combination of narrowband + broadband (the half-width of the emission spectrum is tens of nanometers) or broadband (the half-width of the emission spectrum is hundreds of nanometers) emission can be produced. The main peak of the emission spectrum can vary from nearly 700nm to more than 1000nm. However, it should be pointed out that for a specific matrix material, doping Cr 3+ The subsequent luminescence performance (including the main peak position of the emission spectrum and the half-width of the emission spectrum, and even whether luminescence will occur) is unpredictable in advance. For example, Patent Document 1 (Li Zhanjun, Yu Zimin, Zhou Juanjuan, Gulizabaier Abilipizi, Xu Yicheng, Wang Yuxin, CN115772403A, A Class of Chromium-Thulium Co-doped Blue-violet Light-Converting Narrow-spectrum Near-infrared Fluorescent Materials and Their Preparation and Application) discloses a class of chemical formula ATiO3:Cr x / Tm y Chromium-thulium co-doped blue-violet light-converting narrow-spectrum near-infrared fluorescent material, wherein A is at least one of the elements Ca, Sr, Na, Y, Gd, Ga, Sn, etc., x, y are the molar contents of Cr and Tm elements relative to Ti element, 0<x, y≤0.2. Under the excitation of blue light, the fluorescent material can emit near-infrared light with a peak value of about 800nm ​​and a half-peak width of less than 40nm. Patent document 2 (Liu Ronghui, Liu Yuanhong, Chen Xiaoxia, Ma Xiaole, Gao Wei, Chen Mingyue, CN110857389B, a near-infrared phosphor and a light-emitting device containing the phosphor) discloses a near-infrared phosphor with a chemical composition of A x R p O r :D yA near-infrared fluorescent material, wherein the A element is selected from one or two of Sc, Y, La, Lu and Gd; the R element includes Ga, and one of Al, B and In is added; the D element includes Cr, and one of Ce, Eu, Tb, Bi, Dy, Yb, Pr, Nd and Er is added; and the parameters x, p, r and y meet the following conditions: 0.8≤x≤1.2, 0.8≤p≤1.2, 2≤r≤4, 0.0001≤y≤0.25. The material exhibits broadband emission under blue light excitation, and the main emission peak is located at 700-1600nm. It should be pointed out that the material is composed of Cr 3+ The main peak of the resulting emission spectrum is located at ~800nm. 3+ In the case of elements such as Yb, near-infrared emission with a wavelength of nearly 1000nm will be produced, but Yb 3+ The emission spectrum of Cr is narrow-band, and the half-width of the emission spectrum is only a dozen nanometers. 3+ The emission spectrum after doping (including the main peak position of the emission spectrum and the half-width of the emission spectrum) is completely different.

[0005] At present, some Cr 3+ Non-patent document 2 (Shihai Miao, Yanjie Liang, Dongxun Chen, Ruiqi Shi, Xihui Shan, Yi Zhang, Fei Xie, Xiao-Jun Wang, Site-Selective Occupancy Control of Cr Ions toward Ultrabroad-Band Infrared Luminescence with a Spectral Width up to 419nm, ACS Applied Materials & Interfaces, 2022, 14: 53101-53110) discloses a Cr 3+ The emission spectrum of doped Mg2SiO4 covers 600-1400nm under blue light excitation, and the half-width of the emission spectrum can reach 419nm. Although the half-width of the near-infrared emission spectrum of this material is wide, it should be pointed out that the main peak of the emission spectrum of this material does not exceed 1000nm, so the coverage of the emission spectrum in the near-infrared range is narrow.

[0006] Patent document 3 (Chen Xiaoxia, Liu Yuanhong, Liu Ronghui, Xue Yuan, CN110330970B, a red and near-infrared luminescent material, preparation method and luminescent device) discloses a material that can produce red and near-infrared luminescent materials, the corresponding molecular formula is aSc2O3·Ga2O3·bR2O3, wherein the R element includes one or two of Cr, Ni, Fe, Yb, Nd or Er elements, 0.001≤a≤0.6, 0.001≤b≤0.1. The material can produce luminescence with a wide spectrum of 650 to 1700nm or multiple narrow-band spectra under blue light excitation. However, it should be pointed out that the half-height width of the emission spectrum of the material is usually no more than 150nm, which is relatively narrow, and the coverage of the near-infrared spectrum is narrow.

[0007] Patent document 4 (Liu Quanlin, Mao Ning, Song Zhen, Yu Yi, CN111378445A, a Cr 3+ Preparation and application method of doped near-infrared wide-spectrum luminescent material) discloses a chemical formula of Ca3Y 2-x Ge3O 12 :xCr 3+ A near-infrared broad-spectrum luminescent material, wherein 0.01mol%≤x≤20mol%. The material has an emission wavelength covering 700 to 1200nm under blue light excitation. However, it should be noted that the half-width of the emission spectrum of the material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000nm, and the coverage range of the near-infrared spectrum is relatively narrow.

[0008] Patent document 5 (Feng Jie, Ding Xuemei, Li Yunfeng, Huang Ruitian, Wan Guojiang, CN116376551A, A near-infrared phosphor and its preparation method, near-infrared light-emitting device) discloses a near-infrared phosphor with a chemical formula of A a M b N c O 19 :xD near-infrared fluorescent material; wherein A is one or two of Mg, Ca, Sr, Ba; M is at least two of Ga, Al, B, In; N is a trivalent Sc element; D is Cr 2+ Ion or Cr 3+ Ions can produce emission with a wavelength range of 700-850nm under blue light excitation. However, it should be pointed out that the half-width of the emission spectrum of this material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000nm, and the coverage of the near-infrared spectrum is relatively narrow.

[0009] Patent document 6 (Liu Yuanhong, Liu Ronghui, Chen Xiaoxia, Ma Xiaole, Li Yanfeng, Chen Mingyue, CN110857388B, a near-infrared luminescent material and a luminescent device containing the luminescent material) discloses a composition formula M a A b(QO3)c:zZ near-infrared fluorescent material, wherein the M element is selected from one of Ca, Sr, Ba or Mg, the A element is selected from one of Sc, Y, La, Lu or Gd; the Q element is selected from one or two of Ga, Al, B or In; the Z element includes Cr and one of Ce, Eu, Tb, Bi, Dy, Cr, Yb, Pr, Nd or Er; a, b, c and z meet the following conditions: 0.8≤a≤3.2, 1.8≤b≤3.2, 3.5≤c≤4.5, 0.0001≤z≤0.5. The near-infrared material can absorb blue light well and has broadband or multi-spectral emission in the near-infrared region (700-1700nm). However, it should be pointed out that the half-height width of the emission spectrum of the material does not exceed 200nm, which is relatively narrow.

[0010] Patent document 7 (Jiao Huan, Han Xing, Wang Cuiping, Wang Xiaoming, Xu Ling, CN111647404A, a Cr 3+ Activated broadband near-infrared phosphor and its preparation method) discloses a broadband emission near-infrared phosphor, whose chemical formula is NM2Ga 1- x G5O 14 :xCr 3+ , wherein N is one or a combination of Li, Na, K, and Rb; M is one or a combination of Mg, Ca, Sr, and Ba; G is one or a combination of Si, Ge, and Sn; 0.01≤x≤0.15. The emission wavelength of the fluorescent material covers 650 to 1200 nm. However, it should be pointed out that the matrix structure of the material contains a large amount of alkali metals (Li, Na, K, and Rb), so the water resistance of the material is poor; at the same time, the half-width of the emission spectrum is narrow, and the main peak position of the emission spectrum does not exceed 1000 nm, and the coverage range of the near-infrared spectrum is narrow.

[0011] Patent document 8 (Shao Qiyue, Xu Xiaoxue, Yao Leqi, Dong Yan, Jiang Jianqing, CN110862821B, a phosphate-based phosphor material and its preparation method and application) discloses a phosphor with the chemical formula AB 1-xP2O7:xCr near-infrared phosphor, wherein A is at least one of Li, Na, and K, and 0.01≤x≤0.1. The core preparation method of the material is as follows: the weighed raw materials are fully mixed and then sintered in an air atmosphere, and then the sintered product is ground into powder, washed, and dried to obtain the phosphate fluorescent material. The phosphor described in the present invention can be effectively excited by a blue light LED and emits broadband near-infrared light in the range of 750 to 1100 nm. However, it should be pointed out that the matrix structure of the material contains a large amount of alkali metals (Li, Na, K), so the water resistance of the material is poor; at the same time, the half-width of the emission spectrum of the phosphate-based near-infrared fluorescent material is narrow, and the main peak position of the emission spectrum does not exceed 1000 nm, and the coverage range of the near-infrared spectrum is narrow.

[0012] Patent document 9 (Zhong Jiyou, Zhang Hongshi, Zhao Weiren, CN113481006B, a near-infrared wide-spectrum fluorescent material and its preparation method and application) discloses a chemical formula (M 1 1-m Cr m )M 2 O4 near-infrared wide-spectrum fluorescent material, among which M 1 is selected from Al, Ga, Sc or In, and must contain Al and / or Ga; M 2 The element is selected from Ta or Nb; 0.0001≤m≤0.1. The fluorescent material can be excited by 460nm blue light, and the emission peak is located at 820-920nm and can change continuously. However, it should be pointed out that the half-width of the emission spectrum of the material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000nm, and the coverage range of the near-infrared spectrum is narrow.

[0013] Patent document 10 (Dai Danjie, Li Panlai, Wang Zhijun, Yang Zhiping, CN108531175B, a near-infrared phosphor and its preparation method and application) discloses a near-infrared phosphor with a chemical formula of Mg 3-x Ga2Cr x A near-infrared phosphor of GeO8, wherein 0<x≤0.1. The emission spectrum of the near-infrared fluorescent material covers 700~1200nm. The half-width of the emission spectrum of the material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000nm, and the coverage range of the near-infrared spectrum is relatively narrow.

[0014] Patent document 11 (Ye Xinyu, Han Lei, Nie Wendong, Zhao Yulei, Chen Guang, Zuo Jiaxing, Li Yan, CN112552912A, a new type of Cr 3+ Doped broadband near-infrared phosphor, preparation and application) discloses a chemical formula A 3-y Ca y B 2-x- z C zD3O 12 :xCr 3+ / aRE2O3 (0 < x < 0.5, 1 ≤ y < 3, 0 < x + z ≤ 2, 0 < z < 1.5, 0 ≤ a ≤ 0.5) near-infrared phosphor, where A is one or a combination of several of Lu, Y, Gd, La, etc.; B is one or a combination of several of Mg, Zn, Cu, Ni, Fe, Co, Ti, etc., C is one or a combination of several of Sc, In, Al, Ga, etc., D is one or a combination of several of Ge, Si, Ti, Sn, etc.; RE is one or a combination of several of Yb, Nd, Ce, Er, Pr. This fluorescent material is composed of Cr 3+ The main peak of the emission spectrum generated is located at ~800 nm. When additional elements such as Yb are doped 3+ etc., near-infrared emission with a wavelength close to 1000 nm will be generated, but the emission spectrum of Yb 3+ is narrow-band, and the full width at half maximum of the emission spectrum is only a dozen nanometers. Therefore, relatively speaking, the coverage range of the near-infrared spectrum of this material is narrow.

[0015] Patent Document 12 (Zhong Jiyou, Li Chaojie, Zhao Weiren, Shi Peng, CN114015445A, A garnet-structured near-infrared fluorescent material and its preparation method and application) discloses a near-infrared fluorescent powder with the chemical formula M3In 2-a-b Sc a Cr b Ga3O 12 ; where M is selected from La, Gd, Y or Lu; 0 ≤ a ≤ 1; 0.001 ≤ b ≤ 0.3. Under blue light excitation, the emission peak wavelength of this fluorescent material is located at 720 - 810 nm. It should be noted that the full width at half maximum of the emission spectrum of this material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000 nm, and the coverage range of the near-infrared spectrum is narrow.

[0016] Patent Document 13 (Xia Zhiguo, Liu Gaochao, CN112251226B, A near-infrared light-emitting material and its preparation method and conversion-type led light-emitting device) discloses a general formula of A x B y C z O q D pNear-infrared phosphor, wherein A is Li or Na, B is an element of In, Lu, Sc, Ga, Al, Zr, Ti, Hf, Sn or Ge, C is an element of Sb, Nb, Ta, Zr, Ti, Hf, Sn or Ge, O is oxygen element, D is an element of Mn, Cr, Ni, Bi, Pr, Nd, Tm, Eu, Yb, Er or Ho; 0.8 ≤ x ≤ 1.2, 1.5 ≤ y ≤ 2, 0.5 ≤ Z ≤ 1, 5 ≤ q ≤ 7, 0 < p ≤ 0.2. This near-infrared phosphor can emit light in the range of 780 - 1400 nm, with a peak wavelength of about 970 nm and a full width at half maximum of about 220 nm. Although the full width at half maximum of the near-infrared emission spectrum of this material is relatively wide, it should be noted that this material contains a large amount of alkali metals (Li, Na), so its water resistance is poor. In addition, the main peak of the emission spectrum does not exceed 1000 nm, so the coverage of the emission spectrum in the near-infrared range is relatively narrow.

[0017] Patent Document 14 (Zheng Guojun, Xiao Wenge, Qiu Jianrong, CN113213933B, A broadband near-infrared fluorescent ceramic and its preparation method and application) discloses a broadband near-infrared fluorescent ceramic with a chemical composition of Y 3-x-z A x Al 5-x-y Si x O 12 :yCr 3+ / zYb 3+ . Wherein, A is one or more of the elements of Mg, Ca, Sr, Ba, and the value ranges of x, y, and z are respectively: 0.5 ≤ x ≤ 1.5, 0.005 ≤ y ≤ 0.2, 0 ≤ z ≤ 0.2. The near-infrared spectrum of this fluorescent material covers 650 - 1000 nm. However, it should be noted that the full width at half maximum of the emission spectrum of this material is relatively narrow, and the main peak position of the emission spectrum does not exceed 1000 nm, so the coverage range of the near-infrared spectrum is relatively narrow.

[0018] Patent Document 15 (Shao Qiyue, Ding Hao, Dong Yan, Jiang Jianqing, CN108148593A, A phosphor material for near-infrared LEDs and its preparation method) discloses a near-infrared fluorescent material with a chemical formula of R 1-y X 3-x (BO3)4:xCr / yYb, wherein R is at least one of La, Lu, Gd, Y, Nd, X is at least one of Al, Ga, Sc, 0.005 ≤ x ≤ 0.5, 0.005 ≤ y ≤ 0.2. This fluorescent material can emit near-infrared light with a main peak located within 920 - 1050 nm under blue light excitation. However, it should be noted that the main peak of the emission spectrum generated by Cr 3+ of this fluorescent material is located at ~800 nm. When Yb 3+ is doped additionally, near-infrared emission with a wavelength close to 1000 nm will be generated, but Yb3+ The emission spectrum is narrow-band, and the full width at half maximum of the emission spectrum is only a dozen nanometers. Therefore, relatively speaking, the coverage range of the near-infrared spectrum of this material is narrow.

[0019] Patent Document 16 (Liu Quanlin, Zhao Fangyi, Song Zhen, Zhao Jing, CN109913209B, Cr-doped perovskite-structured halide near-infrared luminescent material and preparation method) discloses a near-infrared fluorescent material with the chemical composition formula AB 1-x X3:xCr 3+ where A:B:X = 1:1:3; A is at least one of Cs and Rb; B is at least one of Ag, Na, In, Ga, and Pb; X is at least one of Cl and Br; 0 < x < 100 mol%. The near-infrared emission spectrum of this fluorescent material covers 800 - 1400 nm, and the emission peak is located around 950 - 1050 nm. However, it should be noted that a large amount of alkali metals (Cs, Rb) are contained in the matrix structure of this material, so its water resistance is poor, and there are certain difficulties in applying it to LED devices.

[0020] Patent Document 17 (Wang Jing, Liu Bomei, CN114656955A, A kind of Cr 3+ / Ni 2+ co-doped broadband near-infrared phosphor and its preparation method and conversion-type LED light-emitting device) discloses a near-infrared fluorescent material with the chemical composition of Mg 1-x-y Ni x Cr y O, where 0 < x ≤ 0.03, 0 < y ≤ 0.03. This fluorescent material uses MgO as the matrix, Ni 2+ as the activator ion, and co-doped with Cr 3+ to optimize the fluorescence performance. The emission spectrum covers 1000 - 1700 nm, and the main peak of the emission spectrum is located at 1335 nm. However, it should be noted that although the coverage range of the near-infrared spectrum of this fluorescent material is relatively wide and the main peak position of the emission spectrum is also greater than 1000 nm, due to the matrix being MgO and the water resistance of the MgO matrix being poor, there are certain difficulties in applying it to LED devices.

[0021] Patent Document 18 (Liang Yanjie, Miao Shihai, CN113583676B, A broadband near-infrared luminescent material and its preparation method and application) discloses a chemical formula of Na 3-z A z Sc 2-x-y-c B c (PO4)3:xCr 3+ / yGa 3+A broadband near-infrared luminescent material, wherein 0<x≤0.10, 0<y≤0.5, 0≤z≤3, A is one or more of Li and K; 0≤c≤2, B is one or more of Lu / Y / Al and La. The near-infrared luminescent material can generate near-infrared light emission with a main peak wavelength of ~750nm under blue light excitation. Although the half-width of the near-infrared emission spectrum of the material is wide, it should be pointed out that the main peak of the emission spectrum of the material does not exceed 1000nm, so the coverage in the near-infrared range is narrow.

[0022] Patent document 19 (Zhou Shifeng, Lin Liting, Luo Hao, Peng Yikai, Zeng Yubin, Zhang Jianwang, Liu Xin, CN106587635A, a Ni 2+ :Cs2SiF6 glass-ceramic and its preparation method and application) discloses a glass-ceramic with a chemical composition of Ni 2+ : Near-infrared microcrystalline glass of Cs2SiF6. The microcrystalline glass is a Cs2SiF6 microcrystalline phase, and the molar percentage of each component is: CsF10-30%, ZnF210-30%, Al2O30-5%, NiO0.1-0.5%, and the balance is SiO2. 2+ The ions are the luminescence center, and the luminescence range is 1200-2200nm, with the luminescence peak at 1500-1600nm. However, it should be pointed out that although the near-infrared light coverage of this fluorescent material is wide and the main peak position of the emission spectrum is greater than 1000nm, the chemical properties of the microcrystalline phase Cs2SiF6 are unstable and not water-resistant, so there are certain difficulties in applying it to LED devices.

[0023] In short, there is still a lack of Cr with a main peak of emission spectrum greater than 1000nm, a half-width of emission spectrum greater than 250nm, stable chemical properties and high quantum efficiency. 3+ It is a near-infrared fluorescent material with luminescence center. Summary of the invention

[0024] The purpose of the present invention is to solve the above problems in the prior art and provide a wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm. 3+ It is an activator and emits near-infrared light under blue light excitation. The main peak of the emission spectrum is greater than 1310nm, and the half-width of the emission spectrum is greater than 300nm. The quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material is applied to near-infrared light LED devices.

[0025] In order to achieve the above object, the present invention adopts the following technical scheme:

[0026] A wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm, the chemical formula of the material is: Ba3Gd 4-xCr x (PO4)6, where 0<x<0.5.

[0027] Preferably, x may be 0.05.

[0028] The second object of the present invention is to provide a method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm, the preparation method comprising the following steps:

[0029] A) mixing a Ba precursor, a Gd precursor, a Cr precursor and a P precursor, and performing a high temperature solid phase reaction under an air atmosphere to obtain an intermediate;

[0030] B) The intermediate is re-grinded and uniformly treated, and a high-temperature solid-phase reaction is carried out under a reducing atmosphere to obtain a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm.

[0031] Preferably, in step A), the molar ratio of Ba, Gd, Cr and P in the Ba precursor, the Gd precursor, the Cr precursor and the P precursor is 3:(4-x):x:6, wherein 0<x<0.5.

[0032] Preferably, in step A), the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Gd precursor is selected from one or more of Gd carbonate, Gd oxide, Gd oxalate and Gd nitrate; the Cr precursor is selected from Cr oxide; and the P precursor is selected from phosphate.

[0033] Preferably, the purity of the Ba precursor, the Gd precursor, the Cr precursor and the P precursor is not less than 99.5%.

[0034] Preferably, in step A), the temperature of the high temperature solid phase reaction is between 600 and 800° C., the atmosphere is air, and the time of the high temperature solid phase reaction is between 2 and 4 hours.

[0035] Preferably, in step B), the reducing atmosphere is ammonia or a nitrogen-hydrogen mixed gas; the temperature of the high-temperature solid phase is between 1350 and 1450° C., and the time of the high-temperature solid phase is between 4 and 10 hours.

[0036] Another object of the present invention is to provide a broadband near-infrared light source, which comprises a broadband near-infrared fluorescent material with a half-width greater than 300nm and an LED chip capable of generating light between 400 and 500nm.

[0037] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0038] The method of the present invention is a wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm, which has a completely new chemical composition and a chemical formula of: Ba3Gd 4-x Cr x (PO4)6, where 0<x<0.5. The material is Cr 3+ It is an activator and emits near-infrared light under blue light excitation. The main peak of the emission spectrum is greater than 1310nm, and the half-width of the emission spectrum is greater than 300nm. The quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material is applied to near-infrared light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the emission spectrum of the material obtained in Comparative Example 1 of the present invention.

[0040] Figure 2 This is the emission spectrum of the material obtained in Comparative Example 2 of the present invention.

[0041] Figure 3 This is the emission spectrum of the material obtained in Comparative Example 3 of the present invention.

[0042] Figure 4 This is the emission spectrum of the material obtained in Comparative Example 4 of the present invention.

[0043] Figure 5 This is the emission spectrum of the material obtained in Comparative Example 5 of the present invention.

[0044] Figure 6 This is the emission spectrum of the material obtained in Comparative Example 6 of the present invention.

[0045] Figure 7 This is the emission spectrum of the material obtained in Comparative Example 7 of the present invention.

[0046] Figure 8 This is the emission spectrum of the luminescent material obtained in Example 1 of the present invention.

[0047] Fig. 9 This is the emission spectrum of the luminescent material obtained in Example 2 of the present invention.

[0048] Fig.10 This is the emission spectrum of the luminescent material obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0049] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0050] The present invention provides a wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm, and its chemical formula is as follows: Ba3Gd 4-x Cr x (PO4)6, where 0<x<0.5.

[0051] In one embodiment of the present invention, x is preferably 0.01; in one embodiment of the present application, x is preferably 0.02; in one embodiment of the present invention, x is preferably 0.03; in one embodiment of the present invention, x is preferably 0.05; in one embodiment of the present invention, x is preferably 0.08; in one embodiment of the present invention, x is preferably 0.1; in one embodiment of the present invention, x is preferably 0.15; in one embodiment of the present invention, x is preferably 0.2; in one embodiment of the present invention, x is preferably 0.25; in one embodiment of the present invention, x is preferably 0.3; in one embodiment of the present invention, x is preferably 0.4; in another embodiment of the present invention, x is preferably 0.48.

[0052] The present invention also provides a method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm, the steps of which are as follows:

[0053] A) mixing a Ba precursor, a Gd precursor, a Cr precursor and a P precursor, and performing a high-temperature solid-phase reaction in an air atmosphere to obtain an intermediate;

[0054] B) The intermediate is re-grinded and uniformly treated, and a high-temperature solid-phase reaction is carried out under a reducing atmosphere to obtain a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm.

[0055] In the above step A), the molar ratio of Ba, Gd, Cr and P in the Ba precursor, the Gd precursor, the Cr precursor and the P precursor is 3:(4-x):x:6, wherein 0<x<0.5.

[0056] In the above step A), the Ba precursor can be a compound containing Ba that is well known in the art and is not particularly limited. In the present invention, the Ba precursor is preferably selected from one or more of Ba carbonates, Ba oxides, Ba oxalates and Ba nitrates, and more preferably is Ba carbonate, i.e., BaCO3; the Gd precursor can be selected from one or more of Gd carbonates, Gd oxides, Gd oxalates and Gd nitrates, and more preferably is Gd oxide, i.e., Gd2O3; the Cr precursor is selected from Cr oxides, i.e., Cr2O3; the P precursor is selected from phosphates, and more preferably is diammonium phosphate, i.e., NH4H2PO4.

[0057] The purity of the above-mentioned Ba precursor, Gd precursor, Cr precursor and P precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained fluorescent material.

[0058] In the above step A), the temperature of the high-temperature solid phase is preferably 600-800°C, and the atmosphere is air atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 700°C.

[0059] In the above step A), the high temperature solid phase time is preferably 2 to 4 hours, more preferably 2 to 3 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 2 hours.

[0060] In the above step B), the temperature of the high temperature solid phase is preferably 1350-1450°C; in some embodiments provided by the present invention, the temperature of the high temperature solid phase is preferably 1400°C.

[0061] In the above step B), the high temperature solid phase time is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0062] In the above step B), the reducing atmosphere can be a dry atmosphere well known to those skilled in the art without any special limitation, and ammonia is preferred in the present invention;

[0063] The high temperature solid phase reaction is preferably carried out in a high temperature furnace; after the reaction is carried out in steps A) and B) in sequence, the furnace is cooled to room temperature to obtain a wide spectrum near-infrared fluorescent material with a half-width greater than 300nm.

[0064] The present invention adopts high-temperature solid-phase reaction to successfully prepare a wide-spectrum near-infrared fluorescent material with a half-width greater than 300nm.

[0065] The present invention also provides a broadband near-infrared light source. The broadband near-infrared light source comprises a broadband near-infrared fluorescent material with a half-width greater than 300nm and an LED chip that can generate light between 400 and 500nm. The specific production steps include: mixing the broadband near-infrared fluorescent material with a half-width greater than 300nm with epoxy resin in a mass ratio of 1:3, applying it to the surface of the LED chip that can generate light between 400 and 500nm, and then curing it at 150°C for 2h to obtain a broadband near-infrared light source.

[0066] In order to further illustrate the present invention, a mixed infrared fluorescent material and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0067] The reagents used in the following comparative examples and embodiments are all commercially available.

[0068] Comparative Example 1

[0069] The raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4. The molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6. The above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high-temperature furnace under air atmosphere, and cooled to room temperature in the furnace to obtain a material.

[0070] The material obtained in Comparative Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 1 As shown in Table 1, the target phase was not obtained because the reaction temperature was too low, so the material did not emit light under the excitation of 450nm blue light.

[0071] Comparative Example 2

[0072] The raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4. The molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under air atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba3Gd 3.95 Cr 0.05 (PO4)6 materials.

[0073] The material obtained in Comparative Example 2 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 2 As shown. Since it has not been sintered twice and has not been sintered in a reducing atmosphere, the material emits weak light under the excitation of 450nm blue light, the main peak of the emission spectrum is located at 900nm, and the half-height width of the emission spectrum is 103nm, which is relatively narrow. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 2, and the quantum efficiency is 0.5%. See Table 1 for details.

[0074] Comparative Example 3

[0075] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0076] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under air atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.95 Cr0.05 (PO4)6 materials.

[0077] The material obtained in Comparative Example 3 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 3 As shown. Since the material was not sintered in a reducing atmosphere, the emission of the material was weak under the excitation of 450nm blue light, the main peak of the emission spectrum was located at 998nm, and the half-height width of the emission spectrum was 179nm, which was relatively narrow. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 3, and the quantum efficiency was 2.3%. See Table 1 for details.

[0078] Comparative Example 4

[0079] The raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4. The molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under ammonia reducing atmosphere. Then, the theoretical chemical composition is Ba3Gd 3.95 Cr 0.05 (PO4)6 materials.

[0080] The material obtained in Comparative Example 4 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 4 As shown. Due to the lack of secondary sintering, the material emits weak light under the excitation of blue light 450nm, the main peak of the emission spectrum is located at 1114nm, the half-height width of the emission spectrum is 197nm, and the half-height width is relatively narrow. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to comparative example 4, and the quantum efficiency is 10.5%. See Table 1 for details.

[0081] Comparative Example 5

[0082] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.4:0.6:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0083] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.4 Cr 0.6 (PO4)6 materials.

[0084] The material obtained in Comparative Example 5 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 5 As shown. 3+ The doping concentration is too high, and concentration quenching occurs. The material emits weak light under the excitation of blue light 450nm, the main peak of the emission spectrum is located at 1366nm, and the half-height width of the emission spectrum is 330nm, which is relatively narrow. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 5, and the quantum efficiency is 5.6%. See Table 1 for details.

[0085] Comparative Example 6

[0086] Step A), the raw materials are BaCO3, Sc2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Sc, Cr and P in BaCO3, Sc2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0087] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Sc 3.95 Cr 0.05 (PO4)6 materials.

[0088] The material obtained in Comparative Example 6 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 6 As shown. When Sc, which is also a rare earth element, is used to replace Gd, similar technical effects are not obtained. The material emits weak light under the excitation of blue light 450nm, the main peak of the emission spectrum is located at 1078nm, and the half-height width of the emission spectrum is 244nm, which is relatively narrow. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 6, and the quantum efficiency is 7.8%. See Table 1 for details.

[0089] Comparative Example 7

[0090] Step A), the raw materials are BaCO3, Lu2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Lu, Cr and P in BaCO3, Lu2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0091] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Lu 3.95 Cr 0.05 (PO4)6 materials.

[0092] The material obtained in Comparative Example 7 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 7 As shown. When Lu, which is also a rare earth element, is used to replace Gd, similar technical effects are not obtained. The material emits weak light under the excitation of blue light 450nm, the main peak of the emission spectrum is located at 981nm, and the half-height width of the emission spectrum is 237nm, which is relatively narrow. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 7, and the quantum efficiency is 8.8%. See Table 1 for details.

[0093] Example 1

[0094] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.99:0.01:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0095] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.99 Cr 0.01 (PO4)6 materials.

[0096] The material obtained in Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 8 As shown. It can be seen that the material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1340nm, and the half-width is 309nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 1 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 90.3%. See Table 1 for details. It can be seen that the material corresponding to Example 1 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be used in near-infrared LED devices.

[0097] Example 2

[0098] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.98:0.02:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0099] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.98 Cr 0.02 (PO4)6 materials.

[0100] The material obtained in Example 2 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Fig. 9 As shown. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1341nm, and the half-width is 311nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 2 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 94.2%. See Table 1 for details. It can be seen that the material corresponding to Example 2 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0101] Example 3

[0102] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.97:0.03:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0103] Step B), the intermediate was re-grinded and mixed, and then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.97 Cr 0.03 (PO4)6 materials.

[0104] The material obtained in Example 3 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1342nm, and the half-width is 312nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency of the material corresponding to Example 3 was tested using a quantum efficiency tester, and its quantum efficiency was 95.7%. See Table 1 for details. It can be seen that the material corresponding to Example 3 is a wide-spectrum near-infrared fluorescent material with a main peak of an emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0105] Example 4

[0106] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.95:0.05:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0107] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.95 Cr 0.05 (PO4)6 materials.

[0108] The material obtained in Example 4 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Fig.10 As shown. It can be seen that the material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1349nm, and the half-width is 316nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 4 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 96.9%. See Table 1 for details. It can be seen that the material corresponding to Example 4 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be used in near-infrared LED devices.

[0109] Example 5

[0110] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.92:0.08:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0111] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.92 Cr 0.08 (PO4)6 materials.

[0112] The material obtained in Example 5 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1350nm, and the half-width is 318nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 5, and its quantum efficiency was 95.7%. See Table 1 for details. It can be seen that the material corresponding to Example 5 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0113] Example 6

[0114] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.9:0.1:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0115] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.9 Cr 0.1 (PO4)6 materials.

[0116] The material obtained in Example 6 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1352nm, and the half-width is 320nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 6 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 93.8%. See Table 1 for details. It can be seen that the material corresponding to Example 6 is a wide-spectrum near-infrared fluorescent material with a main peak of an emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0117] Example 7

[0118] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.85:0.15:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0119] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.85 Cr 0.15 (PO4)6 materials.

[0120] The material obtained in Example 7 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1355nm, and the half-width is 320nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 7 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 92.1%. See Table 1 for details. It can be seen that the material corresponding to Example 7 is a wide-spectrum near-infrared fluorescent material with a main peak of an emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0121] Example 8

[0122] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.8:0.2:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature to obtain an intermediate.

[0123] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.8 Cr 0.2 (PO4)6 materials.

[0124] The material obtained in Example 8 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1357nm, and the half-width is 322nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 8, and its quantum efficiency was 94.6%. See Table 1 for details. It can be seen that the material corresponding to Example 8 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0125] Example 9

[0126] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.75:0.25:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature to obtain an intermediate.

[0127] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.75 Cr 0.25 (PO4)6 materials.

[0128] The material obtained in Example 9 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1357nm, and the half-width is 323nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The material corresponding to Example 9 was tested for quantum efficiency using a quantum efficiency tester, and its quantum efficiency was 96.8%. See Table 1 for details. It can be seen that the material corresponding to Example 9 is a wide-spectrum near-infrared fluorescent material with a main peak of an emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0129] Example 10

[0130] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.7:0.3:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0131] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.7 Cr 0.3 (PO4)6 materials.

[0132] The material obtained in Example 10 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1358nm, and the half-width is 324nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 10, and its quantum efficiency was 90.2%. See Table 1 for details. It can be seen that the material corresponding to Example 10 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0133] Embodiment 11

[0134] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.6:0.4:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature to obtain an intermediate.

[0135] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.6 Cr 0.4 (PO4)6 materials.

[0136] The material obtained in Example 11 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1360nm, and the half-width is 324nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 11, and its quantum efficiency was 90.1%. See Table 1 for details. It can be seen that the material corresponding to Example 11 is a wide-spectrum near-infrared fluorescent material with a main peak of the emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0137] Example 12

[0138] Step A), the raw materials are BaCO3, Gd2O3, Cr2O3 and NH4H2PO4, the molar ratio of Ba, Gd, Cr and P in BaCO3, Gd2O3, Cr2O3 and NH4H2PO4 is 3:3.52:0.48:6, the above raw materials are ground and mixed, loaded into a crucible, sintered at 700°C for 2h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain an intermediate.

[0139] Step B), the intermediate is re-grinded and mixed, then put into a crucible, sintered in a high temperature furnace at 1400°C for 6 hours under an ammonia reducing atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba3Gd 3.52 Cr 0.48 (PO4)6 materials.

[0140] The material obtained in Example 12 was analyzed by a fluorescence spectrometer to obtain its emission spectrum. The material can be excited by 450nm blue light, the main peak of the emission spectrum is located at 1361nm, and the half-width is 325nm. It is a near-infrared luminescent material with an ultra-long emission wavelength. The quantum efficiency of the material corresponding to Example 12 was tested using a quantum efficiency tester, and its quantum efficiency was 90.3%. See Table 1 for details. It can be seen that the material corresponding to Example 12 is a wide-spectrum near-infrared fluorescent material with a main peak of an emission spectrum greater than 1310nm, and the half-width of its emission spectrum is greater than 300nm; the quantum efficiency of the fluorescent material under 450nm blue light excitation is greater than 90%, so that the fluorescent material can be applied to near-infrared LED devices.

[0141] Table 1 Luminescence properties of materials corresponding to comparative examples and examples

[0142]

[0143]

[0144] Example 13

[0145] The chemical composition of the synthesized product of Example 4 is selected as Ba3Gd 3.95 Cr 0.05 A broadband near-infrared fluorescent material with a half-width greater than 300nm of (PO4)6 is uniformly mixed with epoxy resin in a mass ratio of 1:3, and the mixture is coated on a blue light LED with an emission wavelength of 450nm, encapsulated, and then cured at 150°C for 2h to obtain a broadband near-infrared light source. The spectrum coverage range of the broadband near-infrared light source is 690-1850nm.

[0146] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by a person familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.

Claims

1. A wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm, characterized in that: The general chemical formula is: Ba3Gd 4-x Cr x (PO4)6, wherein 0<x<0.5; under the excitation of 450nm blue light, the main peak of the emission spectrum is greater than 1310nm, and the half-width of the emission spectrum is greater than 300nm; the quantum efficiency under the excitation of 450nm blue light is greater than 90%.

2. A wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 1, characterized in that: The x is 0.

05.

3. A method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: A) mixing a Ba precursor, a Gd precursor, a Cr precursor and a P precursor, and performing a high temperature solid phase reaction under an air atmosphere to obtain an intermediate; B) grinding the intermediate again, and carrying out a high-temperature solid phase reaction under a reducing atmosphere to obtain a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm.

4. The method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 3, characterized in that: In step A), the molar ratio of Ba, Gd, Cr and P in the Ba precursor, the Gd precursor, the Cr precursor and the P precursor is 3:(4-x):x:6, wherein 0<x<0.

5.

5. The method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 3, characterized in that: The purity of the Ba precursor, the Gd precursor, the Cr precursor and the P precursor is not less than 99.5%.

6. The method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 3, characterized in that: In step A), the temperature of the high temperature solid phase reaction is 600-800° C., and the reaction time is 2-4 hours.

7. The method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 3, characterized in that: In step B), the reducing atmosphere is ammonia or a nitrogen-hydrogen mixed gas; the temperature of the high-temperature solid phase reaction is 1350-1450° C., and the reaction time is 4-10 hours.

8. The method for preparing a wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in claim 3, characterized in that: In step A), the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Gd precursor is selected from one or more of Gd carbonate, Gd oxide, Gd oxalate and Gd nitrate; the Cr precursor is selected from Cr oxide; and the P precursor is selected from phosphate.

9. Use of the wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm as claimed in any one of claims 1 to 2 or the wide-spectrum near-infrared fluorescent material with a half-width greater than 300 nm obtained by the preparation method of any one of claims 3 to 8, characterized in that: Used in broadband near-infrared light sources.

10. The use according to claim 9, characterized in that: The light source comprises an LED chip with an emission wavelength between 400 and 500 nm.

Citation Information

Patent Citations

  • Ni&lt;2+&gt;:Cs2SiF6 glass ceramic and preparation method and application thereof

    CN106587635A

  • Fluorescent powder material for near-infrared LED (Light Emitting Diode) and preparation method thereof

    CN108148593A

  • A near-infrared phosphor, its preparation method and application

    CN108531175B

  • Cr-doped perovskite-type halide near-infrared luminescent materials and their preparation methods

    CN109913209B

  • Broad-band near-infrared emission luminescent substance and luminescent device containing the same

    CN108913135A